Measurement of Vigilance Using EEG Source Localization - Zeid, Salma Khaled Mohamad (2017)
A Master of Science thesis in Electrical Engineering by Salma Khaled Mohamad Zeid entitled, "Measurement of Vigilance Using EEG Source Localization," submitted in November 2017. Thesis advisor is Dr. Hasan Al-Nashash and thesis co-advisor is Dr. Hasan Mir. Soft and hard copy available.